Frequência, correlatos e perfil neuropsicológico do transtorno da cognição associado com a infecção pelo HIV - Lucas Araujo Lima Geo (2014)
The HIV-associated Neurocognitive Disorders (HAND) is caused by direct action of the HIV virus in the Central Nervous System (CNS) and by indirect action of related metabolic processes associated with the infection - condition that can even drive to dementia. HAND show a pattern described as subcortical which damage white matter brain structures and basal ganglia. Impairment in episodic memory is usually describe in literature and is aim of study by many researchers since is a typical difficulty in Alzheimer's disease. The objectives of this study were characterizing the prevalence of HAND in a hospital population infected with HIV, detect the risk factors and subcortical pattern as well as evaluate the use of auditoryverbal learning test and episodic memory. The overall prevalence of HAND was 71.8% of patients infected with HIV/AIDS. The clinical correlates found were the presence of dyspilidemia, lower hemoglobin level and lower formal educational. The subcortical pattern was observed in HAND; the performance demonstrated typical pattern of impairment in information retrieval strategy but not in storage. The data showed a pattern of high prevalence, risk factors peculiar to the population studied, with subcortical damage characteristics typically described in the literature.